Making choreography, making community. Issue 2 (22nd December 2022) - Ellis, Simon; Raheem, Amaara
Amaara and Simon are choreographers who co-edit Choreographic Practices (along with Dani Abulhawa and Lee Miller). In this editorial they peer into the relationship between making community and practices of choreography and how it might help us rethink the nature of authorship and authority. They talk about their best moves and also call on the work and practices of Sophie Strand, Miranda Tuffnell and D. H. Lawrence to propose that being an artist might be so much more than the first-person pronoun in 'here's something I made'.